Indonesia Natural Rubber Export Competitiveness Analysis in World Export Market - Abednego Victor (Hasanuddin Economics and Business Review, 2023)
This study aims to determine the level of export competitiveness of Indonesia’s natural rubber products, namely TSNR (Technically Specified Natural Rubber), natural rubber latex pre-vulcanized or not, Natural rubber smoked sheets, Mixture of natural rubber latex, and compounded of natural gums. In addition, Comparing Indonesia’s natural rubber competitiveness to Malaysia and Thailand in the ASEAN region. The research method used Revealed Comparative Advantage (RCA) and market share using time series data from 2012 to 2021. There are only four types with good competitiveness with RCA > 1, namely TSNR, Smoked Sheets, Mixture Latex, and Compounded Natural Gums. These four commodities have a comparative advantage with RCA > 1. This shows that Indonesia specializes in these commodities in the world market. Natural rubber TSNR has the highest market share at 41%. The lowest is Natural Rubber Latex and Compounded of Natural Gums at 1%. Indonesia's natural rubber has a comparative advantage or stronger competitiveness than Thailand and Malaysia. This is shown by Indonesia's average RCA value for ten years from 2012 to 2021, which is 30.37. However, Indonesia’s market share has been lower than Thailand’s in ten years.